O Infinitivo Flexionado Do Português Paulista Dos Séculos Xviii, Xix E Xx: Um Estudo Por Meio Das Tradições Discursivas E Do Parâmetro Do Sujeito Nulo - Leite, Sarah Cristina Silva [UNIFESP] (2018)
The Objective Of This Work Is To Propose An Analysis Of The Behavior Of The Inflected Infinitives Of The 18th, 19th And 20th Centuries In The Representative Corpus Of The São Paulo Portuguese. Through The Study Of The Inflected Infinitives (Maurer Jr., 1968, Pires, 2006, Salles, 2006, Modesto, 2011) And Of Diachronic Syntax Studies (Kroch, 1989), Occurrences Of The Phenomena Highlighted In Texts From São Paulo Of The Mentioned Centuries From The Null Subject Parameter (Raposo, 1987; Marins, 2009). This Work Presents A Description Of The Inflected Infinitive In The Corpora Of The Project Of History Of Paulista Portuguese - From The 18th, 19th And 20th Centuries, Through The Following Stages: A) Describe And Analyze The Phenomenon In The Selected Corpus; B) To Establish An Analysis For Inflected Infinitives For The Assignment Of Case And Exceptional Case Marking (Chomsky, 1986; Vergnaud, 2008 [1977]; Preminger, 2015) And The Null Subject Parameter (Duarte, 1995; Figueiredo Silva, 1996 ). The Criteria Used To Se